“Colonialism” and The Fourth World: Notes on Variations in Colonial Situations - Gartrell, Beverley (Culture, 1986)
This paper argues that the increasing use of “colonial” terminology to describe the situation of the peoples anthropologists study has been constructive but has neglected important differences in outcomes of the process of Western colonial expansion. The main section suggests a way of thinking about differences between “external” and “internal” colonies of different types, by focussing on the colonizing power’s changing demands for land and labour, the changing nature of the state, and the role of ideologies defining appropriate treatment of the colonized. The final section speculates on the significance of changing social science terminology in defining the people we study.